Effect of Polystyrene Latex Addition on Size and Pore Volume of Porous Calcium Oxide Particles Prepared by Spray-Pyrolysis Method and Its Ability for SO2 Retention - Septianto, Ricky Dwi; Iskandar, Ferry; Abdullah, Mikrajuddin; Khairurrijal, Khairurrijal; Hwa, Lee Myong (ITB Journal Publisher, LPPM ITB, 2018)
In this study, the effects of polystyrene (PS) latex addition on the particle morphology and the pore content of calcium oxide (CaO) were investigated. The CaO particles were prepared using an ultrasonic nebulizer-assisted spray-pyrolysis method with variation of the PS/Ca(NO3)2·4H2O mass ratio in the precursor. Good crystallinity of CaO was obtained at 825°C of synthesis temperature under 2 l/min of nitrogen gas flow, which was confirmed by Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD). According to scanning electron microscope (SEM) characterization, the CaO particles synthesized with 0 and 25 wt% PS addition had an almost spherical shape with an average size of 1.58 and 1.48 µm, respectively. In addition, macropores were formed in the CaO particles prepared with 25 wt% PS addition that had an average pore diameter of 583.26 nm. Meanwhile, the CaO particles prepared with 75 wt% PS addition had a random shape and an average size of 1.41 µm. The mesopore content was investigated by Barret-Joyner-Halenda (BJH) analysis, which showed improvement of the pore size from 3.45 nm to 5.42 nm for 0 and 25 wt% PS addition, respectively, which is proportional to the pore volume, pore surface area, and the capacity of SO2 retention.